Sistem Pendukung Keputusan Pemilihan Tenaga Fasilitator Lapangan pada Pembangunan Infrastruktur Spald-S Menggunakan Metode Weighted Product - Nur Iman Fitriah; Arita Witanti (Jurnal Syntax Admiration, 2023)
Field facilitators are assistants to community self-help groups in the Infrastructure Development program (SPALD-S). TFL plays an important role in the implementation process technically in the field and administratively. TFL provides supervision, assistance and guidance to KSM leaders and communities receiving MCK assistance. Therefore, field facilitators play a very important role in the implementation process of the SPALD-S Infrastructure development program for MCK construction. The Muna Regency PUPR Service, Southeast Sulawesi, still uses manual calculations to calculate data from participant selection results. This takes a long time, and even results in errors in determining TFL that do not meet the requirements, which results in the implementation of activities in the field technically and administratively. For this reason, a systemized process of calculating data from selection results that has been determined by several specified criteria is needed, with a decision support system to determine field facilitators for SPALD-S infrastructure development using the Weighted Product method. The results of calculating 10 data were ranked in order from highest to lowest, namely A1, A8, A4, A9, A6, A2, A5, A10, A7, and A3. The accuracy value obtained was 53.33%.